2021
DOI: 10.1088/2058-6272/ac35a3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on plasma actuation characteristics of nanosecond pulsed dielectric barrier discharge

Abstract: Combining high-speed schlieren technology and infrared imaging technology, related research has been carried out on the influence of parameters such as actuation voltage, repetition frequency, and electrode size of an actuator on the discharge characteristics, induced flow field characteristics, and thermal characteristics of nanosecond pulsed dielectric barrier discharge. The results show that increasing the value of the actuation voltage can significantly increase the actuation intensity, and the plasma disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Optimizing the actuator geometry [37,38] and the electrical parameters [10,15,30,32,39] can be an effective way to improve the flow control performance of ns-SDBD. It is reported that a negative pulse is more efficient and produces a stronger pressure wave than a positive one under low dissipated power [15,32], and the deposition energy shows a strong dependency on the thickness of the dielectric [29].…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing the actuator geometry [37,38] and the electrical parameters [10,15,30,32,39] can be an effective way to improve the flow control performance of ns-SDBD. It is reported that a negative pulse is more efficient and produces a stronger pressure wave than a positive one under low dissipated power [15,32], and the deposition energy shows a strong dependency on the thickness of the dielectric [29].…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric pressure air dielectric barrier discharge (APADBD) is a burgeoning method for nonthermal plasma generation and has been applied to gas-phase conversion [1][2][3], plasma-assisted combustion [4][5][6], plasma medicine [7][8][9], active flow control [10][11][12], etc. Typically, an alternating current (AC) supply with a frequency of a few kHz is applied to excite APADBD [13].…”
Section: Introductionmentioning
confidence: 99%
“…Based on a combination of high-speed schlieren registration and infrared thermography studies were conducted on the influence of a number parameters (trigger voltage, repetition rate, electrode size) on discharge characteristics, induced the NS-DBD discharge flow fields and thermal characteristics [5]. The electrode surface temperature distributions with a changing flow field for 120 s (the plasma actuator operating time -induced by NS-DBD) were recorded using thermal imaging.…”
Section: Introductionmentioning
confidence: 99%